2015
DOI: 10.15389/agrobiology.2015.4.503eng
|View full text |Cite
|
Sign up to set email alerts
|

Mycotoxin Contamination of Meadow Grasses in European Russia

Abstract: A b s t r a c tA toxicity of plants eaten by animals at grazing land is shown to be complicated with various causes and clinical manifestations. In addition to phytotoxins and «infection» factors carried onto the plants by the insects (e.g., bacterial corynetoxins), the toxic metabolites of endophytic and epiphytic fungi are considered to play the significant role. Based on early understanding, the local risks for cattle, sheep and horses during grazing and stable periods were caused mainly by ergotism, myroth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
20
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 13 publications
3
20
1
5
Order By: Relevance
“…In the present study, for meadow clover and white clover, the results have been confirmed of which we have already reported [17]. Data on the prevalence of mycotoxins in vetches, peas, sweetclovers, alfalfa, lupine and goat's rue were obtained for the first time.…”
supporting
confidence: 91%
See 4 more Smart Citations
“…In the present study, for meadow clover and white clover, the results have been confirmed of which we have already reported [17]. Data on the prevalence of mycotoxins in vetches, peas, sweetclovers, alfalfa, lupine and goat's rue were obtained for the first time.…”
supporting
confidence: 91%
“…For meadow clover, the results coincided with those described earlier [17]. In the preliminary study in 2014, conducted on a collection of 35 samples in the Moscow, Tver regions and the Republic of Karelia, mycotoxins were represented by 12-15 components in all habitats and in different periods of vegetation (July, August and September), and the EMO content was kept ultrahigh (up to 27,540 μg/kg).…”
supporting
confidence: 87%
See 3 more Smart Citations